Design and testing of the JPL‐Nautilus Gripper for deep‐ocean geological sampling. Issue 6 (9th February 2020) - Backus, Spencer B.; Onishi, Rina; Bocklund, Andrew; Berg, Andrew; Contreras, Eric D.; Parness, Aaron
Abstract: We present the design and experimental results for the JPL‐Nautilus Gripper, a 16‐finger highly underactuated microspine gripper for use in the deep ocean. The gripper can grasp objects from 10 to 30 cm in size and anchor to flat and curved rocky surfaces (i.e., cliff faces and seamounts). Laboratory results demonstrated an anchoring capability of greater than 450 N on rough rocks in both shear and normal loading directions. Deployment on the Hercules ROV (remotely operated vehicle) aboard the E/V Nautilus on three deep‐ocean dives verified performance at depths up to to 2, 100 m with approximately 100 N loads applied through the ROV's thrusters, including moment loads. The gripper also serves as a development unit for future robotic tools that will include a coring drill in the center of the gripper, as previously demonstrated in non‐ocean environments with microspine grippers. Such a tool will facilitate the collection of geologic samples from the deep ocean using more agile and cost‐effective systems.